Techno-economic assessment of on-grid solar PV system in Palestine. Issue 1 (1st January 2020) - Ibrik, Imad H.
Abstract: This paper presents the analysis of obtained result from continuous data monitoring of a 41 kWp solar PV system installed on the rooftop of faculty of medicine building at An-Najah National University, Nablus, Palestine (32°13ʹ43.67° N and 35°13ʹ15.72° E). The system was monitored for three years 2016–2018 and it consists of 128 PV panels, an inverter DC/AC, and a grid-connected gross meter. The output electricity feeding to the grid solar electricity is compared and verified with the results from the simulation software program (PVsys) by adopting the installed component specifications, operation conditions, and weather data of the site. The energy generated was fed into the existing power grid and the respective building loads through SMA inverters. The performance parameters of the plant evaluated and compared with other Mediterranean countries, Final Yield (FY) was 1684 kWh/kWp, Reference Yield (RY) was 2046.507 kWh/kWp, and Capacity Utilization Factor (CUF) was found to be 18.5%. The annual average monthly Performance Ratios (PR) for three operating years were 0.88, 0.86 and 0.85, respectively. These indicators provide good feedback for system designers, contractors and energy providers with the actual capacity and feasibility of the system that they can offer the end-users.